Lumberjanes. 6, Sink or swim - Watters, Shannon; Leyh, Kat (Boom! Box, 2017)
Lumberjanes April, Jo, Mal, Molly, and Ripley go on a sea adventure with their mysterious counselor Karen and encounter dangerous storms, shapeshifters, and mysterious portals.